Organosulphur and organoselenium compounds as emerging building blocks for catalytic systems for O-arylation of phenols, a C–O coupling reaction. Issue 21 (10th May 2022) - Sharma, Deepali; Arora, Aayushi; Oswal, Preeti; Bahuguna, Anurag; Datta, Anupama; Kumar, Arun
Abstract : Diaryl ethers form an important class of organic compounds. Abstract : Diaryl ethers form an important class of organic compounds. The classic copper-mediated Ullmann diaryl ether synthesis has been known for many years and involves the coupling of phenols with aryl halides. However, the use of high reaction temperature, high catalyst loading and expensive ligands has created a need for the development of alternative catalytic systems. In the recent past, organosulphur and organoselenium compounds have been used as building blocks for developing homogeneous, heterogeneous and nanocatalysts for this C–O coupling reaction. Homogeneous catalytic systems include preformed complexes of metals with organosulphur and organoselenium ligands. The performance of such complexes is influenced dramatically by the nature of the chalcogen (S or Se) donor site of the ligand. Nanocatalytic systems (including Pd17 Se15, Pd16 S7 and Cu1.8 S) have been designed using a single-source precursor route. Heterogeneous catalytic systems contain either metal (Cu or Pd) or metal chalcogenides (Pd17 Se15 or Cu1.8 S) as catalytically active species. This article aims to cover the simple and straightforward methodologies and approaches that are adopted for developing catalytically relevant organosulfur and organoselenium ligands, their homogeneous metal complexes, heterogeneous and nanocatalysts. The effects of chalcogen (S or Se) donor, halogen (Cl/Br/I) of aryl halide, nature (electron withdrawing or electron donating) of substituents present on the aromatic ring of aryl halides or substituted phenols and position ( ortho or para ) of substitution on the results of catalytic reactions have been critically analyzed and summarized. The effect of composition (Pd17 Se15 or Pd16 S7 ) on the performance of nanocatalytic systems is also highlighted. Substrate scope has also been discussed in all three types of catalysis. The superiority of heterogeneous catalytic systems ( e.g., Pd17 Se15 immobilised on graphene oxide) indicates the bright future possibilities for the development of efficient catalytic systems using similar or tailored ligands for this reaction.